Zhodnocení hospodaření vybrané organizace veřejného sektoru - Marková, Nikol (Vysoké učení technické v Brně. Fakulta podnikatelská, 2018)
Bakalářská práce se zaměřuje na zhodnocení hospodaření příspěvkové organizace, kterou je Základní škola a Mateřská škola Dolní Radechová, okres Náchod. První část práce se zabývá teoretickými poznatky k danému tématu, na kterou následně navazuje druhá část práce zabývající se hospodařením vybrané příspěvkové organizace. Poslední část práce se zabývá návrhy a opatřeními vedoucí ke zlepšení hospodaření dané organizace.

The bachelor thesis focuses on the evaluation of the management of the contributory organization, which is in this case the Primary School and Nursery School in Dolní Radechová, township Náchod. The first part of the thesis deals with the theoretical knowledge about the given topic, followed by the second part of the thesis dealing with the management of selected contributory organization. The last part of the thesis deals with proposals and measures leading to the improvement of the organization's economy.
Evaluation of the Economy of Selected Public Sector Organization
Keywords: neziskový sektor; příspěvková organizace; školství; regionální financování; základní škola; non profit-making sector; allowance organization; education; regional funding; elementary school